Role of protein Tyrosine Phosphatase PTPN22 in T cell signalling and autoimmunity - Sood, Shatakshi (The University of Edinburgh, 2015)
Signals via the T cell receptor (TCR) are critical for the development of T cells in the thymus, maintenance of a self-tolerant peripheral T cell repertoire and the activation of T cells in secondary lymphoid organs. A dynamic balance between tyrosine phosphorylation and dephosphorylation is essential for the maintenance of homeostasis and proper regulation of the immune system. The cytoplasmic phosphatase, PTPN22 (protein tyrosine phosphatase non-receptor type 22) is involved in negative modulation of signal transduction through the TCR and plays a central role in regulating lymphocyte homeostasis. Genome wide association studies reveal that point mutations in PTPN22 confer an increased risk of developing multiple autoimmune diseases in humans. The precise function of PTPN22 and how mutations contribute to autoimmunity is controversial. Loss-of-function mutations in PTPN22 are associated with elevated T effector cell expansion and autoreactive B cells in both humans and mice. A thorough dissection of the molecular involvement of PTPN22 and its allelic variant R619W is important to delineate its role in autoimmunity, to this end we utilised the Ptpn22-/- mice generated in our laboratory. In order to address whether R619W allelic variant is a gain- or loss-of-function mutation, we expressed both PTPN22WT and PTPN22R619W constructs in primary activated Ptpn22-/- T lymphocytes using lentiviral transduction. Surprisingly expression of either wild type or variant phosphatase showed no affect on cytokine production. Preliminary results from bone marrow chimeras generated by retroviral expression of PTPN22WT and PTPN22R619W in Ptpn22 deficient mice showed reduced T cell activation compared to Ptpn22-/- T cells. PTPN22WT appeared to be more suppressive of T cell responses than variant PTPN22R619W. Consistent with studies conducted in comparable knock-in mouse models, our data point to the variant PTPN22R619W as being a partial loss of function allele. To elucidate the mechanism of PTPN22 action in context of an autoimmune disease, we investigated the effect of Ptpn22 deficiency on the phenotype of SKG mice. The SKG mouse harbours a point mutation (W163C) within the carboxyl terminal SH2- domain of ZAP-70, which results in decreased TCR signalling and impaired thymocyte development with defective positive and negative selection. These mice are prone to developing CD4+ T cell mediated autoimmune arthritis that closely resembles rheumatoid arthritis in humans. We found that thymus differentiation was partially restored in SKG Ptpn22-/- thymocytes and Ptpn22 deficiency enhanced TCR mediated signalling in SKG Ptpn22-/- thymocytes relative to SKG thymocytes. Consistent with increased signalling observed in the thymocytes, there was improved in vitro proliferation and IL-2 production of CD4+ T lymphocytes from SKG Ptpn22-/- mice compared to SKG mice. By contrast to SKG mice, SKG Ptpn22-/- mice developed less severe mannan-induced arthritis and showed decreased proportions of Th17 and higher numbers of regulatory T cells. These results show that removal of PTPN22 can compensate, at least partially, for the deficient ZAP-70 activity in the SKG mouse, thus linking PTPN22 and ZAP-70 to the same signalling pathway. This study advances our understanding of how manipulating TCR signals impacts on downstream T cell functions, suggesting PTPN22 may be a valuable target for the treatment of autoimmune diseases. Further studies to determine physiological role of the phosphatase and its disease-associated variants could provide insight into mechanism of immune activation, tolerance and autoimmunity.
Keywords: PTPN22; ZAP-70; SKG mice; T cell signalling; arthritis